Decoding the synergistic mechanisms of functional microbial agents on the microecology and metabolic function in medium-high temperature Daqu starter for enhancing aromatic flavor - Min Zhu; Zhao Deng; Mingyao Wang; Yu Tie; Wenxue Zhang; Zhengyun Wu; Zhengfu Pan; Guorong Luo; Renfu Wu; Jianliang Qin; Katsuya Gomi (Food Chemistry: X)
Utilizing functional Daqu has emerged as an effective strategy to enhance aromatic compounds in Chinese Baijiu. However, research on how functional microbial agents enhance aromatics-producing enzymes and maintain community homeostasis in functional Daqu remains limited. Herein, we reveal the mechanisms of functional microbial agents for enhancing aromatic compounds through reducing interspecies interactions and simplifying the ecological network to drive the aggregated distribution of lactic acid bacteria, and inducing a localized microecology comprised of Aspergillus, Pichia, Millerozyma, Pseudomonas, Paenibacillus, and Rhizomucor, effectively boosting the expression of key enzymes for aromatic synthesis. Functional microbial agents significantly enhance the key enzyme activities (515.9 nmol/h/g and 6.1 U/g for PrAO and ALDH) compared with traditional Daqu (198.6 nmol/h/g and 0.9 U/g), improving the content of aromatic compounds with an increase of 185.57 %. These results revealed the mechanisms of functional Daqu in aromatic compounds production, thus contributing to improve Baijiu quality.